Social Capital and Performance of SMEs: The Mediating Role of Risk-Taking - Erni Masdupi; Rizuwan Abu Karim; Rosyeni Rasyid; Ilham Thaib (School of Business, Bogor Agricultural University (SB-IPB), 2025)
Background: Small and Medium Enterprises (SMEs) are necessary for the Indonesian economy, including SMEs in West Sumatra. They still face various challenges, such as unstable performance and a lack of skills in analyzing risk-taking. A superior business has strategic resources. Resources that can be relied on to achieve stable performance are unique and difficult to imitate. Purpose: The study aims to assess the pertinence of the measurement model with the data and analyze the influence of risk-taking in mediating the nexus of social capital and performance.Design/methodology/approach: Data were collected from 254 managers or owners of SMEs in tourism and the creative economy in West Sumatra. This study employed SEM-AMOS to test the research hypothesis and model.Finding/Results: The results show that the hypothesized measurement model is valid and significant. Social capital is a significant determinant of SMEs' performance and risk-taking. However, risk-taking as an intervening variable of social capital and performance could not be approved in this study.Conclusion: This study concludes that related parties need to pay attention to non-physical resources such as their social capital, which indicates how they have trust, networking, and values that would contribute to the SMEs’ performance.Originality/value (state of art): Previous studies on the determinants of SMEs’ performance have only focused on financial/physical resources but have not considered intangible resources, such as social capital and risk-taking. Keywords: risk-taking, social capital, performance, SMEs, SEM-AMOS